Peran Ibu Dengan Kesiapan Remaja Putri Usia 10-12 Tahun Dalam Menghadapi Menarche - Ni Luh Putu Era Mariani; Sri Subiyatun; Luluk Muhananingsih (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Youthis one component ofthe younger generationthat hasa very important roleand determine thefuture of the nation. Adolescence isa periodfilled withbody changesandmental changes. Understanding and supportof parents is verybeneficial forthe development ofyouth. Panggungharjo village is one of the villagesmost mothers(80%) have not providedan explanation of menarchein adolescentgirls.Objective: To determine the relationship between the role of the mother with readiness of young women aged 10-12 years in the face of menarche in the village Panggungharjo Sewon Bantul Yogyakarta.Method: This research uses descriptive analytic study research design crosssecsional. The populationin this study were all mothers in the village Panggungharjo with girls aged 10-12 years, as many as 50 people, with the total sampling techniques sampling. The variables in this study consisted of the independent variableis the role of mom and the dependent variable is the readiness of young women aged 10-12 years in the facemenarce. The data were taken using a questionnaire.Results: From the analysis of test results bivariate no significant relationship between maternal role with the readiness of young women aged10-12 years in the face of menarche in the village Panggungharjo (0.001<0.05) and the value z Table (2.58) < z (4,5), where the role of the mother is quite the 50% of respondent sand the lack of readiness of young womenin the face of menarche that is 66% of the respondents.Conclusion: There wasa significant association between maternal role with the readiness of young women aged10-12 yearsin the face of menarche in the village Panggungharjo Sewon Bantul Yogyakarta as indicated by the significant value of 0.001 (p <0.05), and the value z Table (2.58) < z (4.5).Keywords: menarche, the role of mother, teenage